A sialic acid-targeted near-infrared theranostic for signal activation based intraoperative tumor ablation. Issue 1 (9th October 2014) - Wu, Xuanjun; Yu, Mingzhu; Lin, Bijuan; Xing, Hongjie; Han, Jiahuai; Han, Shoufa
Abstract : A sialic acid-targeted near-infrared profluorophore with pH-responsive fluorescence and photothermal properties was developed for fluorescence-guided staging and photothermal therapy of viable tumors exposed during surgery. Abstract : Agents enabling tumor staging are valuable for cancer surgery. Herein, a targetable sialic acid-armed near-infrared profluorophore (SA-pNIR) is reported for fluorescence guided tumor detection. SA-pNIR consists of a sialic acid entity effective for in vivo tumor targeting and a profluorophore which undergoes lysosomal acidity-triggered fluorogenic isomerization. SA-pNIR displays a number of advantageous biomedical properties in mice, e.g. high tumor-to-normal tissue signal contrast, long-term retention in tumors and low systemic toxicity. In addition, SA-pNIR effectively converts NIR light into cytotoxic heat in cells, suggesting tumor-activatable photothermal therapy. With high performance tumor illumination and lysosome-activatable photothermal properties, SA-pNIR is a promising agent for detection and photothermal ablation of surgically exposed tumors.